Carbothermal/aluminothermic reduction nitridation synthesis of ZrN–SiAlON refractory composites from zircon and bauxite: a comparative study of the reduction effect of reducers. (3rd April 2017) - Zhang, Zhijie; Wu, Xiaowen; Zhao, Hang; Liu, Jia; Porwal, Harshit; Huang, Zhaohui; Liu, Yan-gai; Fang, Minghao; Min, Xin
ABSTRACT: The ZrN–SiAlON composite refractory powder was successfully synthesised from zircon and bauxite minerals by the carbothermal reduction nitridation or the aluminothermic reduction nitridation method with three typical reducers, including carbon coke, carbon black and aluminium powder. The effect of reaction temperatures on phase composition and microstructure was investigated using X-ray diffraction and a scanning electron microscopy (SEM), respectively. The thermodynamics equilibrium relationships of the condensed phases were analysed as well. The results showed that carbon coke was the most optimum reducer and when it was used as the reducer, the main final products were granular ZrN with a little β-SiAlON. Nevertheless, ZrO2 was produced during reduction at 1600°C when the reducer was carbon black, because the activity of carbon black was the poorest. Additionally, more byproducts were produced in the case of Al powder used as reducer at 1600°C, such as AlN polytype and Al2 O3 .